The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1302/0301-620x.72b4.2380219
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative arthritis after intra-articular fractures of the knee. Long-term results

Abstract: We reviewed 31 of 33 consecutive patients with intra-articular fractures of the knee at 6 to 22 years (average 14). Of these, 77% had excellent or good results; the others had various degrees of degenerative osteoarthritis. There was no significant difference between the results after surgical or conservative treatment. Secondary degeneration was not related to cause or type of fracture, but its incidence increased with the patient's age at the time of injury, though not with the length of follow-up. Early mob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
1
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(84 citation statements)
references
References 0 publications
2
74
1
5
Order By: Relevance
“…Intra-articular fractures and bleeding are associated with OA development 32,33 and repeated bleeds, as seen in hemophilia 34 lead to severe joint damage. It is possible that even a single episode of bleeding in the rabbit joint might contribute to synovial inflammation; fibrin can play a pro-inflammatory role and synovial exposure to blood and hemopoetic cells has been shown to lead to chronic synovitis.…”
Section: Cartilage Degeneration After Bone Injury In a Rabbitmentioning
confidence: 99%
“…Intra-articular fractures and bleeding are associated with OA development 32,33 and repeated bleeds, as seen in hemophilia 34 lead to severe joint damage. It is possible that even a single episode of bleeding in the rabbit joint might contribute to synovial inflammation; fibrin can play a pro-inflammatory role and synovial exposure to blood and hemopoetic cells has been shown to lead to chronic synovitis.…”
Section: Cartilage Degeneration After Bone Injury In a Rabbitmentioning
confidence: 99%
“…In addition sufficient cartilage nourishment is provided with stable fixation and early ROM [11]. Volpin et al reported that early motion might help prevent development of osteoarthritis [14].…”
Section: Introductionmentioning
confidence: 99%
“…the knee increases 3-4-fold after the age of 50 years (2), suggesting that age-related cartilage changes render the tissue incapable of adequately maintaining the extracellular matrix.…”
mentioning
confidence: 99%